In-vitro activity of tigecycline and comparator agents against common pathogens: Indian experience - Veeraraghavan, Balaji; Poojary, Aruna; Shankar, Chaitra; Bari, Anurag Kumar; Kukreja, Seema; Thukkaram, Bhuvaneswari; Neethimohan, Ramya Gajaraj; Bakhtavachalam, Yamuna Devi; Kamat, Shweta (The Journal of Infection in Developing Countries, 2019)
Introduction: Tigecycline Evaluation and Surveillance Trail (TEST) study is an on-going global surveillance. The study was performed to determine the susceptibility of common pathogens to tigecycline and comparator antibiotics by broth microdilution (BMD) at two tertiary care centres in India from 2015 to 2017. Methodology: Total of 989 isolates collected from various clinical specimens between January 2015 and September 2017 from two centres in India were included. BMD was performed to determine the minimum inhibitory concentration (MIC) for tigecycline and comparator antibiotics. Results: Among Gram-negative bacteria, susceptibility to tigecycline was lowest among Klebsiella spp. being 84% while others such as E. coli, Enterobacter spp., Serratia spp. and H. influenzae showed susceptibility of 98%, 95%, 98% and 100% respectively. Overall, 99 isolates among Enterobacteriaceae (E. coli, Klebsiella spp. and Enterobacter spp.) were ESBL producers, susceptible to tigecycline. Among the 101 meropenem resistant Enterobacteriaceae, 85 were susceptible to tigecycline (84%). Among the Gram-positive bacteria, S. aureus and Enterococcus spp. were 99% and 98% susceptible to tigecycline respectively. Among 68 MRSA isolates in the study, 66 (97%) were susceptible to tigecycline. Seven vancomycin resistant E. faecalis were isolated and all were susceptible to tigecycline. Conclusion: Tigecycline has retained activity over both Gram-positive and Gram-negative organisms with MIC values comparable to global reports. About 98% of the MDR Gram-positive and Gram-negative bacteria in the study are susceptible to tigecycline. With increased incidence of extensively drug resistant organisms, tigecycline is a potential reserve drug.